1988
DOI: 10.1521/jscp.1988.6.3-4.423
|View full text |Cite
|
Sign up to set email alerts
|

Lay Beliefs About Overcoming Psychological Problems

Abstract: This study was concerned with laypeople's beliefs about the importance of 24 different contributors toward overcoming four psychological/behavioral problems: agoraphobia, anorexia nervosa, compulsive gambling, and schizophrenia. Factor analysis revealed five almost identical clusters for each problem, which were labeled inner control, understanding, avoidance, physical basis, and fate. Items clustering on the first two factors were thought of as generally important and those on the last three relatively unimpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 8 publications
0
29
1
Order By: Relevance
“…It has been found that lay people generally prefer psychotherapy to drug treatment Angermeyer & Dietrich, 2006) due to the perceived side effects (Angermeyer, Daumer, & Matschinger, 1993;Priest, Vize, Roberts, Roberts & Tylee, 1996;Fischer, Goerg, Zbinden, & Guimon, 1999). There is also a common lay belief that 'will power' can effectively facilitate recovery from mental disorders (Knapp & Delprato, 1980), such as agoraphobia and anorexia nervosa (Furnham & Henley, 1988). However, medication is believed to be the most effective treatment for disorders with a higher perceived severity (Furnham & Rees, 1988;Furnham & Bower, 1992), thus showing that lay and academic theories of treatment overlap to an extent.…”
Section: Lay Theories Of Mental Disordermentioning
confidence: 99%
“…It has been found that lay people generally prefer psychotherapy to drug treatment Angermeyer & Dietrich, 2006) due to the perceived side effects (Angermeyer, Daumer, & Matschinger, 1993;Priest, Vize, Roberts, Roberts & Tylee, 1996;Fischer, Goerg, Zbinden, & Guimon, 1999). There is also a common lay belief that 'will power' can effectively facilitate recovery from mental disorders (Knapp & Delprato, 1980), such as agoraphobia and anorexia nervosa (Furnham & Henley, 1988). However, medication is believed to be the most effective treatment for disorders with a higher perceived severity (Furnham & Rees, 1988;Furnham & Bower, 1992), thus showing that lay and academic theories of treatment overlap to an extent.…”
Section: Lay Theories Of Mental Disordermentioning
confidence: 99%
“…Overcoming Anorexia Nervosa Questionnaire (OANQ; Furnham & Henley, 1988) On this questionnaire, respondents rate the importance on a 0-9 scale of 24 contributors to overcoming AN. Of fi ve factors identifi ed, two (termed Inner Control and Understanding/Help) were deemed 'important' by Furnham and Henley (1988), and three (termed Avoidance; Physical Basis and Fate) relatively unimportant.…”
Section: Eating Disorder Inventory (Edi;mentioning
confidence: 99%
“…Of fi ve factors identifi ed, two (termed Inner Control and Understanding/Help) were deemed 'important' by Furnham and Henley (1988), and three (termed Avoidance; Physical Basis and Fate) relatively unimportant. Vandereycken, 1992) This 30-item scale completed at follow-up, obtains information from parents or spouse about specifi c attitudes or behaviours that may be symptomatic for AN or bulimia.…”
Section: Eating Disorder Inventory (Edi;mentioning
confidence: 99%
“…One plausible explanation for the tendency to attribute the development of paraphilia to childhood relationships could be that it is a reflection of the increasing awareness of childhood abuse and its implications for interpersonal relationships later on in life. Internal control is considered the most important factor for cure, irrespective of the type of paraphilia, as has been found with other psychological problems (Furnham & Henley, 1988;Furnham & McDermott, 1994). Overall, voyeurism seems to differ from all the other problems.…”
Section: Discussionmentioning
confidence: 81%
“…The findings did, to a large extent, confirm the hypotheses; the factor analysis revealed four factors accounting for three quarters of the variance for etiology and three accounting for 60% of the variance for cure, all yielding a satisfactory internal reliability. The different items appeared to fall into groups in a clear and logical fashion (Furnham & Henley, 1988).…”
Section: Discussionmentioning
confidence: 98%